The United States of America Effect on Turkey - European Union Relations - Kirac, Ziya Kivanc; Kisman, Zulfukar Aytac; Sofronie, Bogdan Andrei; Orha, Norina Cristiana (Elsevier Science Bv, 2014)
This article aims at presenting some aspects relating to the international situation which has defined the context in which Turkey has developed its strategies of European accession as well as entrance to a globalised world. It also looks at the position of the USA and how the efforts of the USA influenced Turkey's position regarding EU full membership from the 1980's and until present day. (C) 2014 The Authors. Published by Elsevier B.V.
International Conference on Emerging Markets Queries in Finance and Business -- OCT 24-27, 2013 -- Tirgu Mures, ROMANIA
Keywords: Turkey-EU Relations; Turkey-USA Relations; EU Accession; EU Enlargement; Geopolitics